Pengembangan Media Literacy Board Srikandi Untuk Meningkatkan Literasi Berbasis Budaya Di Jepara - Dewi Nur Agustin (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2024)
The purpose of this study is to develop monopoly media in cultural literacy activities, where researchers develop a monopoly game media which is developed into a media literacy board heroine. The research method used is Research and Development or R&D. Research and Development is a method used for research and development of a product (Sugiyono, 2011:407). The results of this study obtained the results of the paired sample test on the treatment of students which was used to see the difference in the results of the scores of the use of the media literacy board heroine where before and after the treatment, which obtained a significance value (2-tailed) <0.05 which indicated that there was a significant effect on the difference in treatment. assigned to each variable. The results of the analysis of student responses to the use of the heroine board literacy media were carried out in 2 stages at the beginning and at the end of the game. Where in these two stages it can be concluded that the second or last cycle has shown the maximum percentage. So that research on the development of the heroine media literacy board is effectively used for cultural literacy media at SD N 5 Dongos.